2017
DOI: 10.5539/ijbm.v12n8p249
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Asset Structure, Capital Structure, Risk Management and Good Corporate Governance on Financial Performance and Value of The Firm through Earnings and Free Cash Flow As An Intervening Variable in Banking Companies Listed in Indonesia Stock Exchange

Abstract: Banking companies that have gone public has the goal of increasing prosperity of the owners or shareholders by increasing the value of the company. The value of the company is very important because of the high value of the company which will be followed by a high prosperity shareholders. This study aimed to analyze the influence of asset structure, capital structure, risk management and good corporate governance on financial performance and value of the firm through earnings and free cash flow as an interveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 8 publications
1
15
0
3
Order By: Relevance
“…Perhitungan kinerja portofolio dapat diukur berdasarkan Sharpe Index, Treynor's Index, Jensen Index dan Sortino Ratio(Robiyanto et al, 2017; Angriana & Robiyanto, 2018; Santosa dan Sjam, 2012;Tuerah, 2013;Ukhriyawati et al, 2017; Hartono, 2010) yang dirumuskan sebagai berikut:…”
unclassified
“…Perhitungan kinerja portofolio dapat diukur berdasarkan Sharpe Index, Treynor's Index, Jensen Index dan Sortino Ratio(Robiyanto et al, 2017; Angriana & Robiyanto, 2018; Santosa dan Sjam, 2012;Tuerah, 2013;Ukhriyawati et al, 2017; Hartono, 2010) yang dirumuskan sebagai berikut:…”
unclassified
“…Assets structure is one of the aspects relating to the firm resources which describe the assets structure, like the fixed assets, current assets, they are the ownerships of the firm at a certain time for a certain period that can be measured through the following equation: (Desmintari & yetty, 2016;Machali & Setiadharma, 2017;Ukhriyawati et al, 2017).…”
Section: Company Sizementioning
confidence: 99%
“…Other assets ratio to total assets. (Al-Ani, 2014;Ukhriyawati et al, 2017) pointed out that assets structure is a group of tangible assets of the firm in establishing and expanding its tasks and using them in its operations, the tangible assets must be used as insurance to get debt finance from the bank as lenders (Myers, 1977). According to (Titman & Wessels, 1988;Harris & Raviv, 1991) asset tangibility are the main factor in deciding the firm's debt level, and the empirical studies have shown that the assets tangibility is positively related to debt ratio.…”
Section: Company Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The financial performance with GPM indicators and fixed asset turnover has a positive and significant effect on the value of the company in terms of EPS, PBV, and Tobin's Q will increase. The researcher accepted the study of Ukhriyawati, Ratnawati, and Riyadi (2017) and Dwipartha and Witha (2013), which shows the financial performance of a company's value has a positive and significant influence.…”
Section: Propositionmentioning
confidence: 99%